2020
DOI: 10.1007/s00221-020-05810-1
|View full text |Cite
|
Sign up to set email alerts
|

Balance task difficulty affects postural sway and cortical activity in healthy adolescents

Abstract: Electroencephalographic (EEG) research indicates changes in adults' low frequency bands of frontoparietal brain areas executing different balance tasks with increasing postural demands. However, this issue is unsolved for adolescents when performing the same balance task with increasing difficulty. Therefore, we examined the effects of a progressively increasing balance task difficulty on balance performance and brain activity in adolescents. Thirteen healthy adolescents aged 16-17 year performed tests in bipe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 40 publications
(96 reference statements)
3
25
0
3
Order By: Relevance
“…Additionally, following 6 weeks of balance training on an unstable surface (i.e., slackline) Giboin et al [ 23 ] reported decreased H-reflex amplitudes during stepping on a slackline indicating a more anticipatory/feedforward organization of postural control. Another explanation relates to the central nervous plane [ 24 27 ]. For example, Gebel et al [ 24 ] used electroencephalographic analyses to examine the impact of increasing balance task difficulty on cortical activity in adolescents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, following 6 weeks of balance training on an unstable surface (i.e., slackline) Giboin et al [ 23 ] reported decreased H-reflex amplitudes during stepping on a slackline indicating a more anticipatory/feedforward organization of postural control. Another explanation relates to the central nervous plane [ 24 27 ]. For example, Gebel et al [ 24 ] used electroencephalographic analyses to examine the impact of increasing balance task difficulty on cortical activity in adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation relates to the central nervous plane [ 24 27 ]. For example, Gebel et al [ 24 ] used electroencephalographic analyses to examine the impact of increasing balance task difficulty on cortical activity in adolescents. They observed significant increases in the theta frequency band power and decreases in the alpha-2 frequency band power with increasing levels of task difficulty.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of alpha power during the experimental conditions indicated a decrease in alpha-1 and alpha-2 power from stable to unstable conditions. Previous investigations associated these desynchronizations in alpha power with task-specific sensorimotor processing to counteract postural instability (Del Percio et al 2009 ; Hülsdünker et al 2015 ; Gebel et al 2020 ). Accordingly, the present study demonstrated that spectral power in the alpha-1 and alpha-2 frequency band significantly decreased in bilateral motor and right parieto-occipital clusters with increased postural instability.…”
Section: Discussionmentioning
confidence: 96%
“…In the present investigation, the observed increased body sway demonstrated that the postural equilibrium was perturbed by the unstable base of support, leading to increased error detection and processing. Therefore, it maybe speculated that the increase in fronto-midline theta power along with increased postural sway may represent higher attentional demands and error processing to control for postural equilibrium (Fournier et al 1999 ; Slobounov et al 2009 ; Sipp et al 2013 ; Gebel et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation